Morze i woda w filmowych topografiach Gdańska - Ilona Copik (Annales Universitatis Paedagogicae Cracoviensis. Studia de Cultura, 2020)
The purpose of the paper is to analyse film topographies of Gdańsk and investigate the motifs connected with sea and water. I intend to ask myself some questions concerning the ways in which film makers develop aquatic motifs and use waterside location, to what extent film scenery – with water as the dominant element – recreates and creates “the meaning of place”. I treat the sea and water as images and film locations with certain aesthetic, economical and cultural functions. The methodological basis is cultural geography and discovering the relationship film–city–region, film–real and symbolic space, as well as visual anthropology, which makes it possible to capture the methods of coding signs on the screen, pointing to explicit and implicit ideologies, and cultural meanings, constructed in the process of sender– recipient activities. Research material includes selected Polish feature films: Wolne miasto, directed by Stanisław Różewicz (1958); Do widzenia, do jutra, directed by Janusz Morgenstern (1960); Człowiek z żelaza, directed by Andrzej Wajda (1981); Wróżby kumaka, directed by Robert Gliński (2005); Miasto z morza, directed by Andrzej Kotkowski (2009), and others.